Evaluation of the anticancer potential of secondary metabolites from Pseudevernia furfuracea based on epidermal growth factor receptor inhibition. Issue 24 (17th December 2022) - Kalra, Rishu; Conlan, Xavier A.; Gupta, Manish; Areche, Carlos; Bhat, Mamta; Goel, Mayurika
Abstract: UHPLC/ESI/MS/MS profiling followed by bioactivity guided isolation of Pseudevernia furfuracea ( P. furfuracea ) extract yielded two polyphenolic molecules, Methyl haematommate (PF-1) and Atraric acid (PF-2). These molecules were evaluated for bioactivity against five cancerous cell lines. The results revealed that atraric acid showed significant activity against ovarian cancer cell line (PA-1) having GI50 at 16.42 µg/mL and moderate activity against the breast cancer cell line (MCF-7), having GI50 at 64.35 µg/mL. The results were further supported by in silico molecular docking studies of atraric acid with the epidermal growth factor receptor (EGFR) tyrosine kinase protein. The study revealed that atraric acid has the capacity to act as a potential EGFR inhibitor via occupying the ATP binding pocket of EGFR and making favourable electrostatic interactions and van der Waals interaction with its key residues. Our results highlight P. furfuracea and its polyphenolic compound, atraric acid as a promising candidate for ovarian cancer management. Graphical Abstract: UF0001